Institutional Drivers of Internet Voting Adoption in Ghana: A Qualitative Exploratory Studies - Agbesi, Samuel (Nordic and Baltic Journal of Information & Communications Technologies, 2020)
Internet voting system adoption in elections can bring enormous benefits to an electoral process. Though few countries have adopted it for their legally binding elections, others have discontinued its use because of perceived vulnerabilities. But it has been argued that the benefits the internet voting system provide outweigh the perceived vulnerabilities. The main purpose of this study is to examine the drivers of the internet voting system from the organizational context. The study is purely qualitative using semi-structured interviews. The interview participants were top management of EC staff, political parties’ executives and experts who were purposively selected, and thematic analysis was used to extract patterns from the data collected. The main themes that emerged from the thematic analysis include pressure from political parties, pressure from the government, legal framework, financial readiness of EC, EC top management support, convenience, accuracy, and increase voter turnouts. The discussion of the findings and the implication of the results were discussed in the study.